Research Progress on the Application of Ultrasound in Food Processing - Shiyang LIANG; Ying ZHANG; Xiaofang ZENG; Weidong BAI; Wenhong ZHAO (Shipin gongye ke-ji, 2023)
In the process of food processing, traditional processing methods can no longer meet people's high demand for food quality. Ultrasonic technology is a non-heat treatment technology that can reduce the damage caused by conventional food processing to enhance food's nutritional value and processing characteristics. This paper mainly discusses the effects and functions of ultrasonic waves in processing operations such as drying, freezing, extraction, filtration and emulsification. The cavitation, mechanical, chemical and biological effects of ultrasonic waves can affect processing operations through complex correlations. For example, it can improve mass transfer and heat transfer efficiency, reduce processing time, reduce the dosage of processing reagents, increase yield, enhance food safety, and preserve food nutrition. By combing and comparing the literature, ultrasonic technology has been of great application value in food processing operations, but inappropriate ultrasonic conditions can also negatively affect food quality. In future work and research, it is necessary to establish the dynamic model of ultrasonic in food processing and dig deep into the application at the industrial level to overcome the shortcomings of ultrasonic energy consumption.